PENGARUH KUALITAS PRODUK DAN KREDIBILITAS ENDORSER (AGNEZ MO) TERHADAP MINAT BELI KONSUMEN SAMPO CLEAR (STUDI PADA KONSUMEN SAMPO CLEAR DI PERUMAHAN TATA SURYA JL.VENUS) - Dian Nafilatul Maulida; N. Rachma; M. Hufron (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACT The purpose of this study was to determine the effect of product quality variables and endorser's credibility on buying shampoo clear interest in consumers in the solar system of Jalan Venus. the research method used is quantitative. The population and sample used in this study are consumers of clear shampoo who reside in the residential solar system Jl.Venus. sampling using purposive sampling, and in this study using multiple linear regression analysis method. The results of this study provide evidence of product quality variables and endorsers' credibility both simultaneously and partially influencing consumer buying interest Keywords: product quality, endorser credibility, buying interest